Arrhythmia-Associated Calmodulin E105A Mutation Alters the Binding Affinity of CaM to a Ryanodine Receptor 2 CaM-Binding Pocket - Angelos Thanassoulas (2822861) (2023)
Calmodulin (CaM) is a small, multifunctional calcium (Ca2+)-binding sensor that binds and regulates the open probability of cardiac ryanodine receptor 2 (RyR2) at both low and high cytosolic Ca2+ concentrations. Recent isothermal titration calorimetry (ITC) studies of a number of peptides that correspond to different regions of human RyR2 showed that two regions of human RyR2 (3584-3602aa and 4255-4271aa) bind with high affinity to CaM, suggesting that these two regions might contribute to a putative RyR2 intra-subunit CaM-binding pocket. Moreover, a previously characterized de novo long QT syndrome (LQTS)-associated missense CaM mutation (E105A) which was identified in a 6-year-old boy, who experienced an aborted first episode of cardiac arrest revealed that this mutation dysregulates normal cardiac function in zebrafish by a complex mechanism that involves alterations in both CaM-Ca2+ and CaM-RyR2 interactions. Herein, to gain further insight into how the CaM E105A mutation leads to severe cardiac arrhythmia, we generated large quantities of recombinant CaMWT and CaME105A proteins. We then performed ITC experiments to investigate and compare the interactions of CaMWT and CaME105A mutant protein with two synthetic peptides that correspond to the two aforementioned human RyR2 regions, which we have proposed to contribute to the RyR2 CaM-binding pocket. Our data reveal that the E105A mutation has a significant negative effect on the interaction of CaM with both RyR2 regions in the presence and absence of Ca2+, highlighting the potential contribution of these two human RyR2 regions to an RyR2 CaM-binding pocket, which may be essential for physiological CaM/RyR2 association and thus channel regulation. Other Information Published in: International Journal of Molecular Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ijms242115630